2011
DOI: 10.1007/s12602-011-9081-8
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and Characterization of Putative Probiotic Bacterial Strain, Bacillus amyloliquefaciens, from North East Himalayan Soil Based on In Vitro and In Vivo Functional Properties

Abstract: This study is aimed to isolate some novel probiotics from the soils of North East Himalayas. Eleven Gram positive isolates were obtained in MRS with Oxgall media from soil samples. Four of the isolates withstood the in vitro gastric juice pH 3.0 and 0.45% bile salt tolerance screening. Among these, PBT 3 showed high cell surface hydrophobicity and adhered to the Caco-2 cells. 16s rDNA gene sequences of this probiotic strains were identified as Bacillus amyloliquefaciens (accession no: JF836079). In in vivo bio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(14 citation statements)
references
References 42 publications
1
13
0
Order By: Relevance
“…Probiotic bacteria can regulate lymphocyte cytokine production and inflammatory responses [ 60 ]. Hairul Islam et al [ 61 ] reported that BA could alleviate increased concentrations of pro-inflammatory mediators, such as TNF-α and IL-1β in a mouse model of colitis induced by dextran sulfate. The results of the present study further corroborate the ability of BA to temper IUGR-induced excessive secretion of TNF-α in the small intestine, which may be due to the simultaneous increase in IL-10 content after administration of BA.…”
Section: Discussionmentioning
confidence: 99%
“…Probiotic bacteria can regulate lymphocyte cytokine production and inflammatory responses [ 60 ]. Hairul Islam et al [ 61 ] reported that BA could alleviate increased concentrations of pro-inflammatory mediators, such as TNF-α and IL-1β in a mouse model of colitis induced by dextran sulfate. The results of the present study further corroborate the ability of BA to temper IUGR-induced excessive secretion of TNF-α in the small intestine, which may be due to the simultaneous increase in IL-10 content after administration of BA.…”
Section: Discussionmentioning
confidence: 99%
“…This probiotic ameliorated the damage caused by inflammation in dextran sulphate sodium (DSS)-induced colitis in mice ( Hairul Islam et al, 2011 ) and LPS-induced stress in broilers ( Li et al, 2015 ) by down-regulating expression of pro-inflammatory cytokines such as TNF α , IL1 β and IL2 and up-regulating the anti-inflammatory cytokine IL10 upon exacerbated inflammation. In addition, a decrease in neutrophil myeloperoxidase and an increase in antioxidant molecules (superoxide dismutase and catalase) was observed ( Hairul Islam et al, 2011 ). In the present study, superoxide dismutase and catalase were not measured, but the observed decrease in oxidative radicals measured with the respiratory burst assay indirectly reflects this anti-oxidant effect.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Islam et al isolated a B . amyloliquefaciens strain from soil, and demonstrated it had a beneficial effect on inflammatory bowel disease [ 23 ]. Larsen et al reported a B .…”
Section: Introductionmentioning
confidence: 99%